Valor nutricional do feno de Andropogon gayanus colhido em diferentes idades - Andre Cayo Cavalcanti (2014)
It was aimed to evaluate the nutritional value of the Andropogon gayanus grass hays harvested at 56, 84 and 112 days of growth. The experimental design was completely randomized and means were compared by Studant-Newman-Keuls at 5% level of significance. In chapter 3 in situ degradability of nutritional components, was observed that the average ruminal disappearance of dry matter, organic matter, crude protein, neutral detergent fiber and acid detergent fiber, after 96 hours of ruminal incubation, were higher (P<0.05) for the hay made with the plant harvested at 56 days of regrowth. Chapter 4, with the semi-automatic in vitro technic of gases production, was observed that the accumulated gases production by the Andropogon gayanus grass hays harvested at 56 days was higher than the others treatments at 24, 48 hours of incubation (P<0.05), and the same treatment had higher (P<0.05) degradability for the dry matter and the organic matter in all of the fermentation times evaluated. In the Chapter 5, was evaluated the energy partition and the methane production in sheeps fed with Andropogon gayanus grass hays in three different ages of cut. The intakes of digestible energy were lower (P<0.05) for the animals receiving the oldest material. The values of the digestible energy of the Andropogon gayanus grass hays as that the treatment hay at 56 days had the highest (P<0.05) value and the material made at 84 and 112 days resulted in lower (P>0.05) value. The methane production by the fermentation of the hay material did not differ (P>0.05) between the three treatments measured. It was conclude that the best age to cut the Andropogon gaynus grass for hay is at 56 days of growth.